Penggunaan Trash Can-Composter (TCC) Untuk Pengolahan Sampah Organik Dan Penghasil Kompos Bagi Warga Desa Tanah Wulan, Bondowoso - Wika Amini, Helda; Syarifah, Ratna Dewi; Maulina, Wenny; Shofa, Ghaitsa Zhahira; Sholihah, Athaya Farras; Prasetyani, Tiana Febrianti Eka; Ma'rifah, Binti Ni'matul; Setiawan, Dimas Arif; Syaifullah, Rangga Yudha (Dedikasi:Jurnal Pengabdian kepada Masyarakat, 2024)
Have been done for assistance in waste processing using a trash can-composter (TCC) machine and making compost provided to the residents of Tanah Wulan Village, Maesan District, Bondowoso. This service activity is carried out with the aim of providing education to the community regarding good waste management and recycling waste to be used as a compost planting medium. Through this service activity, the person running this program, called kader ibu-ibu rumah tangga (IRT), was formed in Tanah Wulan Village, chaired by Ibu Asnawati as the leader of the Waste Management. Waste from household waste and harvest residues, such as vegetable waste, straw and rice husks, is chopped using a TCC machine. The chopped results are mixed with cow dung, sawdust and EM4 starter to get useful compost. The content of the compost produced is tested and ready to be applied to plants.Keywords: Trash can-composter, organic waste, compost